STRATEGI PENERAPAN KREDIT BANK SYARIAH MANDIRI TERHADAP PETANI KARET DI KECAMATAN LUBUK RAJA KABUPATEN OKU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2018)
This study aims to find out the strategy of applying the credit of sharia banks to rubber farmers in the sub-district of king kabpaten OKU. however, the method used in this study is a randomized, unbalanced method, with data analysis with SWOT strategy. The results of this research are several strategies, among others, strategy which is done when power faced with opportunity (S-O strategy) at Bank Syariah Mandiri KC Baturaja is Improving multipurpose financing and product with application of latest technology to all rubber farmers in general. (S3, O1, 02). Strategy is done when the existing strength in Bank Syariah Mandiri met with threat (Strategy S-T) that is: Using profit sharing system so that at the moment of fluctuation of credit rubber price at farmer keep running smoothly (S1, T1). The strategy undertaken when Bank Syariah Mandiri is in the weakness of meeting with the opportunity (WO strategy) is: to socialize in various media about Syariah banking principles so that it can attract customers as much as possible in general (W1, O1, O2), Opening branch or dissemination of Bank office Syariah Mandiri especially in Baturaden for easy access and easy credit to farmers in general. (W2, O2), W-T's strategy is to conduct promotional strategies and provide information on financing and good management of farmers (W1, T2).